Nasal Glial Heterotopia: An Unusual Cause of Lump on the Nose in a Child- A Case Report - Suchitra Pusapati; Uma Divya Tejaswini Gudipudi; Krishnam Raju Penumetcha (Indian Pediatrics Case Reports)
Background: Glial heterotopia is a rare, nonneoplastic extracranial displacement of the brain tissue, most commonly seen on the nose. Clinical Description: A 2-year-6-month-old boy presented with a nasal mass gradually increasing since birth, being otherwise asymptomatic. The mass was firm, tense, predominantly skin-colored with some bluish discoloration, with no signs of inflammation, present on the left side of the bridge of the nose. Systemic examination and vitals were normal. Management and Outcome: Contrast-enhanced magnetic resonance imaging scan showed features suggestive of nasal glial heterotopia (NGH), with a thin linear T2-weighted hyperintense stalk extending from the mass up to the foramen cecum. Complete surgical excision, with ligation and cauterization of the fibrous communicating tract, was done close to intracranial entry. Histopathology confirmed the diagnosis of glial heterotopia, with immunohistochemistry showing glial fibrillary acid protein positivity. Conclusion: Pediatricians need to be aware that a slow-growing external nasal mass, present since birth, may be a NGH. Imaging can delineate intracranial connections with confirmation by histopathology after complete excision.